PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN : STUDI KASUS PADA PT. PRAYASA INDOMITRA SARANA TAHUN 2012 – 2014 - Hamidi, Hamidi (MEASUREMENT : Jurnal Program Studi Akuntansi, 2015)
This studyaimed todetermine the effectof working capital(cash turnoverandinventory turnover) on profitability(ROE) at PT. PrayasaIndomitra sarana.The objectof thisresearchstudyisa company engaged inthe distribution offuel, namely PT. PrayasaIndomitraSarana. The financial statements ofthe dataused is thecompany's financial statementsfor 3years, from2011-2014.The methodused onthisresearchis themethod ofmultipleregression analysis. From the researchthatworking capital turnoverhave an influence onprofitability.whereasforcash turnoverandinventory turnoverhas anegativebutnot significanteffecton profitability.Keywords : ROE, CTO